LANGUAGE STYLE AND GENRE ANALYSIS OF EULOGY A Eulogy by Lee Hsien Yang at the Funeral Service of Mrs. Lee Kuan Yew - Bagus Dwi Pambudi (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2018)
This study aims at investigating the role of language as well as its characteristics and genre components in eulogy involving social function, generic structure, and linguistic features in eulogy. The eulogy analyzed was delivered by Lee Hsien Yang, the son of former Singapore Prime Minister, at the funeral service of Mrs. Lee Kuan Yew at Mandai Crematorium on October 6th, 2010. Employing discourse analysis, focusing on how the text is structured in terms of the sequence of words, clauses, sentences, and paragraph to unveil language style and genre components of eulogy. Although it is delivered orally, the eulogy can be regarded as written text based on several considerations such as one-way communication (monologic organization), context independence, synoptic organization, polished draft through the use of standard grammar and formal language, nominalization and lexical density. The eulogy purposes to commemorate someone deceased by praising and giving high honor, and it is generally in the form of speech (a piece of writing) in memorial service. The structure consists of initial event leading to other events/memories, sequence of events in particular time and place, and conclusion which functions to paraphrase the speaker’s feeling towards someone he/she loves. Eulogy also has distinct features such as the use of past tense, focusing on specific participants, the use of material processes, circumstances of time in initial position, and the use of evaluative words. Key words: language style, genre, eulogy